2021
DOI: 10.1002/adbi.202000106
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Cell‐Loading Injectable Hydrogel Scaffold Significantly Promotes Tissue Regeneration In Vivo Compared with a Conventional Physical Cell‐Loading Hydrogel Scaffold

Abstract: Currently, one of the major tendencies to be adopted for the design of hydrogel scaffolds in tissue engineering include that cells are loaded physically into the pores of 3D hydrogel networks. In this study, a drastic deviation from this tendency is proposed and developed a new type of hydrogel scaffold in which cells are covalently connected to 3D hydrogel networks via bioorthogonal click cross‐linking reactions of azide‐modified cells with alkyne‐modified polymers. The purpose of this study is to directly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Based on this concept, we recently developed a new type of biohybrid hydrogel in which individual living cells are covalently connected through a three-dimensional polymeric gel network (Figure 1). 38,39 In the present study, as a proof-of-concept, we demonstrate the unique self-healing capability of CxGel, which originates from cadherin-mediated intercellular adhesion between cells incorporated into the CxGel. This study is the first example of a self-healing material in which biologically derived living cells are incorporated into a synthetic material as a focus to promote self-healing.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…Based on this concept, we recently developed a new type of biohybrid hydrogel in which individual living cells are covalently connected through a three-dimensional polymeric gel network (Figure 1). 38,39 In the present study, as a proof-of-concept, we demonstrate the unique self-healing capability of CxGel, which originates from cadherin-mediated intercellular adhesion between cells incorporated into the CxGel. This study is the first example of a self-healing material in which biologically derived living cells are incorporated into a synthetic material as a focus to promote self-healing.…”
mentioning
confidence: 51%
“…Based on this concept, we recently developed a new type of biohybrid hydrogel in which individual living cells are covalently connected through a three-dimensional polymeric gel network (Figure ). , This cell cross-linked hydrogel was designated CxGel. Because individual cells are covalently connected through the gel network in CxGel, we expect that the mechanically conductive gel network would permit the transmission of individual cell–cell adhesion force generated at the interface of CxGels to the whole CxGel via an extendable cascade, resulting in a macroscopic adhesion of the whole CxGel.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously proposed a universal technique to construct human cell-based biohybrid hydrogel materials in which azide-modified living cells are chemically (covalently) cross-linked with alkyne-modified polymers via the bio-orthogonal click reaction. Currently, many researchers have reported various cell-surface modification methods, including chemical conjugation, lipid insertion, and metabolic glycoengineering. , The chemicals can be stably introduced to the cell membrane by chemical conjugation, though it is concerned that this method could affect cell viability by interfering with the function of membrane proteins. In the case of lipid insertion, the chemicals can be inserted physically within cell membranes via hydrophobic interactions without interference with membrane protein’s function.…”
Section: Introductionmentioning
confidence: 99%
“…Considering these advantages, we utilized metabolic glycoengineering to form cell cross-linked hydrogels in this study. Since we have demonstrated that this covalent cellcombining approach results in enhanced retention of the material's "livingness" in the body in comparison with the conventional physical cell-combining approach, 18 we hypothesized that the cell cross-linked hydrogel system can be adapted for constructing stem cell-combining biohybrid materials suitable for in vivo tissue engineering applications. In this study, we developed a novel ADSC-based cross-linked hydrogels (ADSCxGels) (Figure 1) and showed its utility as a living stem material for in vivo tissue engineering.…”
Section: Introductionmentioning
confidence: 99%